Peningkatan Motivasi Belajar IPAS pada Materi Fotosintesis melalui Penerapan Model Problem Based Learning (PBL) Berbantuan Media Audiovisual - Siti Soleha; Ribut Prastiwi Sriwijayanti; Ludfi Arya Wardana (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
This study aimed to improve students’ learning motivation in Integrated Science and Social Studies (IPAS) on the topic of photosynthesis through the implementation of the Problem-Based Learning (PBL) model supported by audiovisual media. The study was motivated by the low level of students’ learning motivation, which was reflected in their limited participation, lack of curiosity, and minimal involvement during the learning process. This research employed the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, consisting of two cycles with four stages: planning, action, observation, and reflection. The participants were 17 fourth-grade students of SDN Curahsawo. Data were collected through observation, learning motivation questionnaires, tests, and documentation. The findings revealed that the implementation of the PBL model assisted by audiovisual media successfully enhanced students’ learning motivation in each cycle. The percentage of learning motivation increased from 40.44% in Cycle I Meeting I to 60.88% in Meeting II. Furthermore, in Cycle II, it increased to 79.26% in Meeting I and reached 81.76% in Meeting II. In addition to the quantitative improvement, positive behavioral changes were observed, including increased participation in discussions, greater willingness to ask questions, improved collaboration, and higher engagement in completing learning tasks. Therefore, the implementation of the Problem-Based Learning model supported by audiovisual media was proven effective in enhancing students’ learning motivation in learning photosynthesis among fourth-grade elementary school students.